Isolation, genotyping and virulence determination of a Toxoplasma gondii strain from non‐human primate from China. Issue 2 (31st March 2021) - Xin, Shilin; Jiang, Nan; Yang, Liulu; Zhu, Niuping; Huang, Wei; Li, Junbao; Zhang, Longxian; Su, Chunlei; Yang, Yurong
Abstract: Toxoplasma gondii infects almost all warm‐blooded animals, including humans and non‐human primates. Many cases of T. gondii infection in non‐human primates have been reported worldwide. In this study, 15 monkeys were collected from zoos in Henan Province between 2016 and 2019. A modified agglutination test (MAT) (cut‐off: 1:8) showed that 46.7% (7/15) of the heart juices had T. gondii IgG antibody transformation. One viable T. gondii strain was successfully isolated from the myocardium of a rhesus monkey by bioassay in mice. This strain was designated as TgMonkeyCHn1. The DNA of T. gondii tachyzoites was obtained using cell cultures, and the genotype of this strain was determined by PCR‐RFLP with 10 markers and the virulence genes ROP5 and ROP18 . The genotype and ROP18/ROP5 (3/6) of TgMonkeyCHn1 did not match any known genotypes. In addition, the TgMonkeyCHn1 formed low number of tissue cysts and was non‐lethal to mice. To our knowledge, this is the first T. gondii strain isolated from Old World monkeys. Rhesus monkey is a new host record for T. gondii .